The Natural Grassland Vegetation Types in Relation to the Climatic Factors. (<Special Feature>Ecological Consideration for the Distribution of Natural Grassland Vegetation Zones in Relation to the Climate and Climate Change in Japan) - 西村, 格; 佐々木, 寛幸; 西村, 由紀 (日本草地学会, 2001)
application/pdf Our previous paper showed that the zoning of the Japanese grassland vegetation based upon the climate corresponds to the range of Zoysia japonica-type grasslands, Sasa-type grasslands, Pleioblastus chino-type grasslands. In the present paper we examined the relationships between these types of grassland and the climate factors. The border between the subarctic zone and the cool-temperate zone corresponded to the northern limit of Zoysia japonica type grasslands. In latitudinal distribution, this border corresponded roughly with the line that the coldness index is -35℃・month and that the average minimum temperature of the warmest month is 17℃. However, in altitudinal distribution, this border transferred to the cooler and higher-latitude zone. Futher investigation on the climate index of the altitudinal border is needed. The border between the warm-temperate zone and the subtropical zone corresponded to the southern limit of Zoysia japonica-type grassland and the northern limit of Zoysia tenuifolia-type grassland. This border corresponded roughly with the line that the warmth index is 170℃・month or that the annual mean temperature is 19℃. It was indicated that the border between the cool-temperate zone and warm-temperate zone was the southern limit of Sect. Macrochlamys Nakai, Sect. Sasa (Eusasa Nakai) and Sect. Grassinodi Nakai and the northern limit of Pleioblastus chino. This border was suggested to correspond to the line that the warmth index is 80-85℃・month and that the maximum snow depth is 40 cm. According to the distribution of grassland vegetation based upon the climatic factors in the present study, the distribution of the cool-temperate zone grassalnd including the subalpine zone was expressed to be wider than that of the actual grassland. This can be corrected by taking account the growth limit of Zoysia japonica-type grasslands in higher altitude at each latitude into consideration.The relationship withthe climaticfactors still remaines to be solved. Article journal article